Liveness, mediation and the simulated: Effects of the digital screen on architectural representation post–1990 - Audisho, Endriana (Interstices: Journal of Architecture and Related Arts, 2020)
This paper explores the interplay between the digital screen and its effects on architectural representation from the early 1990s to the early 2000s. The introduction of the computer through the 1994 Paperless Studios at Columbia University’s Graduate School of Architecture, Planning and Preservation (GSAPP) became a defining moment for the discipline to speculate on the effects of the digital screen on architectural representation, specifically the tension between the simulated and the real. Recognising that the relationship between the digital screen and architectural representation is relative to, and has been shaped by, the broader media context of the decade the Paperless Studios is situated in relation to two mediatised events. The first is Cable News Network’s (CNN) 24-hour live coverage of the Gulf War in 1991, and second is the 2002 competition to design the new World Trade Centre (WTC) post the historic attacks of 9/11. Each of these events presents a shift in the tension between the simulated and the real.